The Effect Of Length Of Storage By Giving Lime Juice On The Number Of Bacterial In Domestic Chicken Meat - Wulansari, Nadya Treesna; Padmiswari, AA Istri Mas; Antari, Ni Wayan Sukma (Metamorfosa: Journal of Biological Sciences, 2022)
The study aims to identify effect of length of storage by giving lime juice on the number of bacterial in domestic chicken meat. Experiments with a completely randomized design model were used in this study. The results is indicated that there was an effect of length of storage by giving lime juice on the number of bacteria in domestic chicken meat. The content of organic acids, citric acid, essential oils and limonene contained in lime juice affects the total bacteria found in domestic chicken meat. Domestic chicken meat with lime juice which was stored at <4 0 C for 12 days tended to have an increasing in the number of bacteria contaminants. However, the total number of bacterial plates in domestic chicken meat did not exceed the quality standard limit of the microbial contamination level issued by the Indonesian National Standardization Agency, which is 1 x 10 6 CFU / g. The number of bacteria in domestic chicken meat based on the length of the storage will tend to increase   Keyword : length of storage, lime juice, bacteria, domestic chicken meat